KEDUDUKAN AKTA HIBAH ORANG TUA KEPADA ANAKNYA SEBAGAI PEMBAGIAN WARIS DIHUBUNGKAN DENGAN ASAS MASHLAHAH - Wijaya, Pringgo A; Sayehu, Sayehu; Mustofa, Usman (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2024)
Law is a social rule or norm that cannot be separated from the social norms that exist in society. The family is an important part of society which has a big role in conveying good teachings and values ​​to its members in living life in society. One of the problems that often arises in the family context is related to the transfer of inheritance or assets from parents to children. The gift method is often used by parents with the aim of avoiding conflicts regarding the distribution of inheritance in the future. In this journal, researchers use the statue approach method and by studying the Civil Code (KUH Per) and the Compilation of Islamic Law (KHI) as well as the sources of Islamic law, the Qur'an and Hadith. The formulation of the problem discussed in this journal is the granting of grants and the position of grant deeds. By using the Normative juridical method, this research aims to provide an in-depth understanding of the provisions for granting gifts and distribution of inheritance according to the Compilation of Islamic Law (KHI) and the Civil Code (KUHPer). Thus, it is hoped that this research will provide significant benefits for scientific development in the legal field, as well as provide a contribution in the form of deeper thinking and understanding regarding the procedures for granting grants and the things that can cancel them. Through a normative juridical approach, this research will likely examine in detail the articles related to granting and distribution of inheritance in the Compilation of Islamic Law (KHI) and the Civil Code (KUHPer). The research will also likely identify the principles underlying inheritance law in the two pieces of legislation, as well as compare the similarities and differences between the two. Thus, it is hoped that the results of this research will provide writers and readers with a more comprehensive understanding regarding the procedures for granting gifts and dividing inheritance from the perspective of Islamic law and civil law, as well as highlighting things that can invalidate grant giving. Apart from that, this research can also provide new views or recommendations related to increasing effectiveness and fairness in the application of the law